Pengembangan Game Eco-Tech Gamified Tours sebagai Akselerasi Aset Wisata Industri Ramah Anak Kampung Industri Tempe Sanan - Qolbi, Muhammad Syifa'ul; Roziqin, Mohamad Firzon Ainur; Surya, Eka Putri; Prasetyo, Abdul Rahman; Aruna, Alby; Marcelliantika, Adinda; Wijaya, Ginanjar Atma (VISA: Journal of Vision and Ideas, 2024)
The development of Eco-Tech Gamified Tours as an acceleration of child-friendly industrial tourism assets in the Sanan Tempe Industrial Village aims to enhance the appeal and educational value of tourism for children. This program integrates gaming technology with interactive tours that educate visitors about the tempe production process and the importance of environmental sustainability. Methods include game design and development, integration of educational elements, training for tour guides, and effectiveness evaluation through user feedback. Results indicate a significant increase in children's interest and engagement during tours. The implementation of this program is expected to support the development of innovative and sustainable industrial tourism in the Sanan Tempe Industrial Village.